Idiopathic Hypertension with Multiple Cranial Nerve Palsies: A Case Report and Literature Review - Shasthara Paneyala; Harsha Sundaramurthy; Sahana Panambur; Nemichandra S. C.; Vimala Colaco; Sri Harsha Chalasani (Oman Medical Journal, 2024)
We report a rare case of idiopathic intracranial hypertension (IIH) with multiple cranial nerve palsies involving cranial nerves VI, VII, IX, and X in a 32-year-old female who had no prior comorbidities. Her condition improved rapidly on a ten-day regimen of acetazolamide and tablet topiramate. IIH should be considered in every patient presenting with persistent headache and multiple cranial nerve abnormalities. This paper also includes a literature review of similar cases.